PERFORMANCE RANKING OF TURKISH INSURANCE COMPANIES: THE AHP APPLICATION - (:unkn) unknown (EDITURA ASE, 2014)
Insurance sector performance is important at the stage of economic growth. On the other hand, in practice it is not sufficient to evaluate the options according to the simplest form of decision making only based on a criterion. In such cases, we must consider all the variety of different information to decide to best option. It arise the requirement of multi-criteria decision making methods. The Analytic Hierarchy Process (AHP) is a multiple criteria decision-making methodology designed to help decision makers in prioritizing decisions that involves both tangible and intangible criteria and has been implemented extensively all over the world. The paper employs the AHP to evaluate the performance of insurance companies in Turkey during the period 2006-2010. The main starting point for this study is to evaluate the performance of the insurance companies in Turkey. Turkish insurance industry's financial ratios are placed in a hierarchical decision structure to calculate financial performance score for the insurance companies in Turkey. We used AHP as a systematic methodology of acquiring knowledge from experts through group decision-making. The selected companies are prioritized based on financial criteria using AHP. In other words, based on this analysis the decision-makers can also predict the likelihood of a ranking of insurance companies in Turkey. Sensitivity analysis was performed using Expert Choice. Ranking was sensitive to capital, liquidity and shares-in-sector ratios. In other words, small change in the importance of these criteria caused rank reversal of certain insurance companies. In this paper, the insurance companies performance score was constructed by using publicly open financial data. This framework can be used to select the insurance companies to invest in Turkish Insurance Sector.
Keywords: AHP; financial ratios; performance ranking; Turkish insurance sector